Innova Technology (A): Seeking a market for anti-loss devices - NARASIMHALU, Arcot Desai (Institutional Knowledge at Singapore Management University, 2013)
This case is the first part of a two-part series on Innova Technology, a technology start-up company based in Singapore. The two cases focus on: Case (A) – Developing, producing and marketing a product innovation Case (B) – Growth strategies for a young technology company The case is set in May 2012, and begins with the protagonist, Rick Tan, chief executive officer of Innova Technology Private Limited, contemplating what his company’s go-to-market strategy should be. Tan and his business partner, Jonathan Lim, who is also the Chief Technology Officer for Innova Technology, developed PROTAG, a new anti-loss device, using Bluetooth technology. The device, which is about the size of two credit cards stacked together, is synched to a mobile phone and can be attached to valuable personal belongings such as keys, wallets, handbags, passports and even phones. If the valuable item were to be separated from the person by more than a certain distance, the device would set off an alarm alerting the owner of its potential loss. Tan and Lim are two young entrepreneurs who set up Innova Technology in January 2011 as a technology start-up under the auspices of Singapore Management University’s Institute of Innovation and Entrepreneurship. Tan, the partner with the business and finance skills, focused on developing a sound business plan and raising funds for their product. Lim, the technology guru, channelled his efforts to fine-tune the technology and develop a design with unique functionality. After extensive market research and encouraging results from beta test sales using the crowdfunding site IndieGoGo, Tan had confidence in his product. Yet, he was keenly aware that a great product could fall flat in the market if it was not backed by a well-designed marketing strategy. The partners had invested in manufacturing and 5,000 pieces of PROTAG had already been shipped out from the factory. The business’s budget was wearing thin and Tan had one shot to get his marketing plan right. Tan had to decide on the most appropriate go-to-market strategy for PROTAG: Should he mass market the product or focus on a specific consumer segment? Which segment or segments should he focus on? Should he use multiple sales channels or stick to just one? Which was the most appropriate channel for his product? What price should he charge?